Antimicrobial Bacteria and Viruses Detected Through Systematic Sampling in the Childcare Environment. (October 2020) - Chedid, Khalil; Hayashi, Michael; DeJonge, Peter; Yancey, Olivia; Siebert, Elliane; Getz, Amy; Eisenberg, Joseph; Hashikawa, Andrew; Martin, Emily
Abstract : Background: Approximately two-thirds of children aged <5 years receive out-of-home child care. Childcare attendees have an increased risk of infections compared to children not in childcare settings, possibly due to their close contact in a shared environment. As multidrug-resistant organisms (MDROs) increasingly move from healthcare-associated to community settings, childcare can provide a venue for further transmission of these pathogens. Our objective was to evaluate the bioburden of pathogens present on fomites in childcare centers and how surface contamination changes over time. Methods: The study was conducted in the single-room play area of an Ypsilanti, Michigan, childcare center caring for children aged 3–5 years. Polyester swabs were used to collect surface samples from 16 locations in the room, including (1) laminate, wood and plastic tabletops and furniture; (2) a stainless steel sink and adjacent plastic trash bin; and (3) wood, metal and plastic toys. A water sample was also collected at a 17th site. Samples were collected twice weekly for 5 of 6 weeks, followed by 1 additional collection (September–October 2019). Tryptic soy agar was used for standard plate counts and selective media were used to identify methicillin-resistant Staphylococcus aureus (MRSA), Vvancomycin-resistant Enterococcus (VRE), and extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae . Single-plex RT-PCR was used to detect norovirus and adenovirus. Results: Among 175 samples collected on 11 days, MRSA and ESBL-producing Enterobacteriaceae were detected from 10.3% (18 of 175) and 8.0% (14 of 175), respectively, of environmental specimens. No specimens were positive for VRE or norovirus. Adenovirus was detected in 20 of 175 specimens (11.4%). Median bioburden by site ranged from 85 CFU/mL to 2, 510 CFU/mL. The highest median bioburden was observed at the sink (2, 510 CFU/mL), followed by the plastic building block table (1, 620 CFU/mL), the small wood blocks (1, 565 CFU/mL) and water from a water play area and an adjacent tabletop (1, 260 and 1, 100 CFU/mL respectively). The highest single day bioburden was 273, 000 CFU/mL at the sink. Conclusion: The presence of MDROs on childcare center fomites raised concern for exposure to these pathogens among vulnerable populations. More study is needed to determine the degree to which these contaminated fomites drive transmission between children. We found the highest bioburdens on sites where children played or washed with water, identifying potential targets for more frequent cleaning. Funding: None Disclosures: Emily T. Martin reports a consulting from Pfizer.